DOI: 10.33915/etd.4146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heating, breathing, hair style, posture, and air velocity on breathing zone concentrations for an anthropometrically-correct manikin in a wind tunnel

Abstract: In partial fulfillment of the requirements for the degree of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Since C nose and C mouth were correlated each other, the effects of V face on average C nose ( Figure 5.8) were very similar to the effects of V face on average C mouth ( Figure 5.9). For the range of V face = 100 to 220 fpm, C nose and C mouth dropped consistently as V face increased, which is in general agreement with previous studies (Li et al, 2007;Elnahas, 2005;Guffey and Barnea, 1994;He, 2010). This agreement suggests that V face is an important factor affecting levels of airborne contaminants in the breathing zone for the simple manikin.…”
Section: Effect Of V Face On C Nose and C Mouthsupporting
confidence: 91%
See 3 more Smart Citations
“…Since C nose and C mouth were correlated each other, the effects of V face on average C nose ( Figure 5.8) were very similar to the effects of V face on average C mouth ( Figure 5.9). For the range of V face = 100 to 220 fpm, C nose and C mouth dropped consistently as V face increased, which is in general agreement with previous studies (Li et al, 2007;Elnahas, 2005;Guffey and Barnea, 1994;He, 2010). This agreement suggests that V face is an important factor affecting levels of airborne contaminants in the breathing zone for the simple manikin.…”
Section: Effect Of V Face On C Nose and C Mouthsupporting
confidence: 91%
“…The breathing zone is supposed to be a volume throughout which concentrations are all equal to the inhaled concentrations. Different concentrations at different points in what would be considered in the "breathing zone" were reported by Elnahas (2005). The tested sample locations were the right collar, left collar, right lapel, left lapel, mouth, nose, forehead, center chest, and neck.…”
Section: Manikin In Free-stream Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The dependent variables include the concentrations of the contaminant within the breathing zone (CBZ) of the operator and the concentrations of the contaminant located far downstream within the duct (Cduct). Since previous studies (Elnahass, 2005;Kasberger, 2012) found sampling at the mouth and nose to be redundant, the breathing zone samples were collected at a single point between the mouth and nose.…”
Section: Methodsmentioning
confidence: 99%